(untitled) (AYUSHDHARA, 2018)
Retinitis pigmentosa (RP) defines a clinically and genetically diverse group of diffuse retinal dystrophies initially predominantly affecting the rod photoreceptor cells with subsequent degeneration of cones with a prevalence of 1:5000. It appears in the childhood and progresses slowly, often resulting in the blindness in advanced middle age. In Kaphavidagdha drushti the patient will be able to visualize in a better way because of Kaphalpata in day time, when this Dushita kapha enters Tritiya patala, there manifests Naktandhyata. A male patient aged 28 years approached our OPD complaining of progressive diminution of vision since 10 years. Visual loss started with Nyctalopia further gradually affecting the peripheral vision in the day time. Even colour vision was also affected; among the primary colours he feels difficulty in recognizing blue colour. On fundoscopic examination, pallor disc with attenuated blood vessels and bony specules were found and he was diagnosed as a case of Retinitis pigmentosa. After proper assessing Rogi and Roga bala, treatment was adopted as explained by our Acharyas in the line of Kaya shodana, Shira shodana, Kriyakalpas and Rasayana prayogas. The chemical constituents and other phytonutrients of the drugs used in this case has the ability to cross the ocular barriers and thereby giving good results in treating this patient thereby improving the quality of life of the patient.